Protein Quality Analysis of Baby Porridge, Soybean Protein Concentrate, Rebon and Casein Against Weight Gain in Experimental Rats - Anna Henny Talahatu (International Journal of Social Service and Research, 2023)
Protein quality is assessed based on the speed of growth that occurs after consuming and digesting something protein and the amount of nitrogen absorbed or used by the body. Complete protein can ensure good body growth and can maintain or replace damaged body tissues while incomplete protein although it cannot guarantee growth but is able to maintain body tissues. The purpose of this study to determine high-quality protein food sources can be seen from the value of protein quality indicators, including Protein Efficiency Ratio (PER), Biological Value (BV), Net Protein Utilization (NPU), Net Protein Ratio (NPR), True Digestibility (Dt) and Apparent Digestibility (Da). The research design developed in this study is an experiment using experimental mice with indicators of weight gain and protein quality in some foods. The results showed that the average weight gain (8.5 gr) of the largest rats was rats given baby porridge in their diet, as for weight loss (-2.4 gr) of rats given soy protein concentrate (KPK) in their diet. Furthermore, from the assessment of protein quality, it is known that the highest PER value is baby porridge (10.03), the highest BV value is soy protein concentrate (KPK: 0.99), the highest NPU value is soy protein concentrate (KPK: 1.28) and casein (1.23), the highest NPR value is baby porridge (0.13) while the Dt value (protein / casein 1.36) and Da for all types of protein tested are almost the same.